Quels murs pour quelle école ? Architecture scolaire, normes scolaires et figures d’élèves - Anne Dizerbo (Éducation et Socialisation)
This paper aims to contribute to knowledge on the impact of secondary schools architecture on the building of school norms and pupils profiles. It also questions the relationship between these schools and the urban architecture in which they are located. Interviews with 15-year-old pupils were conducted and interpreted from the hermeneutical perspective of biographical research in education. Data interpretation highlighted the close relation between school’s architecture, its establishment within an urban structure and the building of school norms and students’ profiles.